A Digital Tv-Based Distributed Image Processing Platform for Natural Disasters - Marin-Caihuan, J; Manriquez-Lopez, M (Institute of Electrical and Electronics Engineers Inc., 2019)
After a natural disaster strikes people spontaneously respond by self-organizing, providing food and drink to the victims and to emergency response teams. During this process, people also share photos, messages and videos which can be used to improve the general understanding of the situation and to support decision-making. In this context, we propose to use digital television to create a community of digital volunteers who can help to identify objects inside images that cannot be processed automatically. Digital television can help to reach a larger number of digital volunteers because it can be easily used without installing special applications. We present a distributed platform composed of a server, a network of digital volunteers and an internet service provider. Our proposed platform aims to reduce the communication between the server and the digital volunteers and to reduce the workload of the server. We simulate our proposed platform with the peersim tool. © 2019 IEEE.